President De Klerk and ethos - Johann Cornelius de Wet (Communicare)
This article deals with State President De Klerk's historic opening address before Parliament on 2 February 1990. The focus is on the speak er's ethos as essentially conceptua Ilsed by Aristotle in his Rhetoric, and as it has evolved in modern public speaking in the oratory setting. The evaluation is an exercise in rhetorical criticism based on the artistic stan dard and neo-Aristotelian approach. Both verbal and non-verbal messages are considered. The author con. cludes that Mr De Klerk's display of ethos was credible insofar as he con veyed expertness (Intelligence), trust worthiness and good will during the speech. In fact, given the principles of (Western) democratic politics, no South African State President or Prime Minister has ever reached out with so much apparent good will to the vast majority of South Africans.